2009
DOI: 10.1007/s00127-009-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mental disorders in refugees and native Danes: a register-based retrospective cohort study

Abstract: Refugees have high rates of various mental disorders. Healthcare services should target refugees' mental health from arrival in the receiving country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 20 publications
4
86
0
1
Order By: Relevance
“…The latter group includes migrants who were 'born in labour immigrant countries', thus encompassing traditional labour migrants as well as family reunification migrants, which makes it somewhat more similar to our study group but still not identical. The findings on mental disorders among mixed groups of first generation migrants vary from studies focusing solely on rates among refugee populations (Hermansson et al 2002;Lie 2002;Norredam et al 2009;Steel et al 2002). These studies show even higher rates of mental disorders compared with those of non-migrants; not surprisingly, the highest rates among refugees are seen for nervous disorders, including post-traumatic stress disorder (PTSD).…”
Section: Our Findings In Perspectivementioning
confidence: 65%
See 2 more Smart Citations
“…The latter group includes migrants who were 'born in labour immigrant countries', thus encompassing traditional labour migrants as well as family reunification migrants, which makes it somewhat more similar to our study group but still not identical. The findings on mental disorders among mixed groups of first generation migrants vary from studies focusing solely on rates among refugee populations (Hermansson et al 2002;Lie 2002;Norredam et al 2009;Steel et al 2002). These studies show even higher rates of mental disorders compared with those of non-migrants; not surprisingly, the highest rates among refugees are seen for nervous disorders, including post-traumatic stress disorder (PTSD).…”
Section: Our Findings In Perspectivementioning
confidence: 65%
“…These studies show even higher rates of mental disorders compared with those of non-migrants; not surprisingly, the highest rates among refugees are seen for nervous disorders, including post-traumatic stress disorder (PTSD). In a recent study (Norredam et al 2009) of refugees in Denmark deriving from the same cohort as the current study population of family reunification migrants, we found a significantly increased risk of having a first-time psychiatric contact for combined and specific disorders among refugees compared with non-migrants. Our finding that Iraqi men had a higher risk of nervous disorders most likely stems from their coming from conflict stricken areas and, therefore, being more likely to be traumatised, as is the case for refugees.…”
Section: Our Findings In Perspectivementioning
confidence: 96%
See 1 more Smart Citation
“…31 In contrast, systematic reviews and meta-analyses confirm that refugees are at substantially higher risk than the general population for a variety of specific psychiatric disorders -related to their exposure to war, violence, torture, forced migration and exile and to the uncertainty of their status in the countries where they seek asylum -with up to 10 times the rate of post-traumatic stress disorder as well as elevated rates of depression, chronic pain and other somatic complaints. 22,[32][33][34][35] Exposure to torture is the strongest predictor of symptoms of post-traumatic stress disorder among refugees. 35 Strong evidence shows that some groups of migrants have an elevated incidence of psychotic disorders after migration.…”
Section: How Does Migration Affect Mental Health?mentioning
confidence: 99%
“…An additional and extraordinary stressor playing an important role in the development of mental disorders in general and anxiety disorders in particular is migration [15,16,17,18,19,20,21]. Many studies underline a significant variation in the prevalence of anxiety disorders within the same ethnic group depending on migration status, so that an epidemiological consideration of migrants as a separate collective appears essential [22,23,24].…”
Section: Introductionmentioning
confidence: 99%